Android recipes : - Smith, Dave (Apress, 2015)
It offers pragmatic advice that will help you get the job done quickly and well. This can save you a great deal of work over creating a project from scratch! Android continues to be one of the leading mobile OS and development platforms driving today's mobile innovations and the apps ecosystem. Android appears complex, but offers a variety of organized development kits to those coming into Android with differing programming language skill sets.